2020
DOI: 10.1002/jcp.29720
|View full text |Cite
|
Sign up to set email alerts
|

A Slug‐dependent mechanism is responsible for tumor suppression of p53‐stabilizing compound CP‐31398 in p53‐mutated endometrial carcinoma

Abstract: Mutation in the tumor suppressor gene p53 is the most frequent molecular defect in endometrial carcinoma (EC). Recently, CP‐31398, a p53‐stabilizing compound, has been indicated to possess the ability to alter the expression of non‐p53 target genes in addition to p53 downstream genes in tumor cells. Herein, we explore the alternative mechanisms underlying the restoration of EC tumor suppressor function in mutant p53 by CP‐31398. A p53‐mutated EC cell was constructed in AN3CA cells with restored or partial loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Mechanistically, in response to DNA-damaging agents, the transcriptional complex p300-mut-p53-NF-Y is formed on the promoter of the EFNB2 gene to facilitate its transcription ( Alam et al, 2016 ). Stabilization of otherwise mutated p53 with small molecules can contribute to Mdm2-mediated degradation of Slug and cause apoptosis of endometrial cancer cells also occurring with the participation of PUMA ( Figure 3 ) ( Liu et al, 2020 ). On the other hand, in p53-positive colorectal cancer cells that undergo the EMT program, a protein complex between Vimentin and wild type p53 is formed that prevents the translocation of p53 into the nucleus and hence inactivates its transcriptional activity.…”
Section: Effects On Emt Via Signalling Pathways Re...mentioning
confidence: 99%
“…Mechanistically, in response to DNA-damaging agents, the transcriptional complex p300-mut-p53-NF-Y is formed on the promoter of the EFNB2 gene to facilitate its transcription ( Alam et al, 2016 ). Stabilization of otherwise mutated p53 with small molecules can contribute to Mdm2-mediated degradation of Slug and cause apoptosis of endometrial cancer cells also occurring with the participation of PUMA ( Figure 3 ) ( Liu et al, 2020 ). On the other hand, in p53-positive colorectal cancer cells that undergo the EMT program, a protein complex between Vimentin and wild type p53 is formed that prevents the translocation of p53 into the nucleus and hence inactivates its transcriptional activity.…”
Section: Effects On Emt Via Signalling Pathways Re...mentioning
confidence: 99%
“…As a cell cycle checkpoint, p53 can recognize cells with aberrant mutation, arresting the cell cycle, inhibiting cell growth and inducing cell apoptosis ( 30 ). Several p53 mutations or deficiencies have been revealed in malignant cells, enabling cancer cells to escape and proliferate ( 15 ). TGF-β1 is a pleiotropic cytokine that has been regarded as a double-edged sword in the progression of cancer ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protein p53 is a key cell division checkpoint-monitoring DNA mutant ( 14 ). The function of p53 in cancer is usually impaired or mutated, which enables abnormal cell proliferation ( 15 ). Our previous studies reported that p53 may induce apoptosis in H22 cells ( 13 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of CC cells with these two plant extracts has been shown to significantly reduce MDM2 expression; however, the exact biological mechanisms are still unclear [ 202 ]. In addition, another MDM2-targeting small-molecule compound, CP-31398, a synthetic styrene quinazoline, was able to down-regulate MDM2 expression and restore p53 mutant function in EC [ 205 ].…”
Section: Treatmentmentioning
confidence: 99%